Immunosuppressive treatment adherence in kidney transplanted patients: a literature review - Zanetti, Helen Kris; Gnatta, Diego; Rodrigues, Mariana Ferraz; Oliveira, Luciana Mello de; Heineck, Isabela; Keitel, Elizete; Garcia, Valter Duro (Brazilian Journal of Transplantation, 2012)
Introduction: Kidney transplant recipients require the use of immunosuppressive drugs to block the immunological response and prevent rejection. Adherence to immunosuppressant treatment is essential for graft survival. The increased incidence of rejection and the resulting graft loss are strongly associated to the no adherence. Purpose: Review the literature regarding immunosuppres- sive therapy no adherence in kidney transplant recipients. Methods: A survey of the literature from January 2002 to October 2012 in the PubMed, Lilacs and SciELO database. Results: There is no consensus on the definition and classification of no adherence. The prevalence ranges between articles (1.6 to 50%). Different methods are used to measure no adherence. Multiple factors influence the occurrence of no adherence and, consequently, there is higher incidence of poor clinical and economic outcomes. Interventions in- volve multidimensional approaches and the inclusion of the clinical pharmacist in a multidisciplinary transplant team is proven to be favorable. Conclusions: It is necessary to standardize the nomenclature and the definition of no adherence. It must be determined which is the most accurate combination of measurement methods. A review of predictive factors for no adherence should contain a sample representing all types of patients, and should facilitate the design for risk profiles. The intervention effectiveness should be tested by randomized studies. The assessment of no adherence, risk factors and outcomes needs to be performed by prospective lon- gitudinal studies